2010
DOI: 10.1093/europace/euq107
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of atrial fibrillation: does the addition of three-dimensional magnetic resonance imaging of the left atrium to electroanatomic mapping improve the clinical outcome?: A randomized comparison of Carto-Merge vs. Carto-XP three-dimensional mapping ablation in patients with paroxysmal and persistent atrial fibrillation

Abstract: Image integration using Carto-Merge in patients undergoing catheter ablation for paroxysmal and persistent AF does not significantly improve the clinical outcome, but shortens the X-ray exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(63 citation statements)
references
References 24 publications
1
58
0
4
Order By: Relevance
“…747,1186,1248,1249 This can only be achieved, however, by an awareness of the importance of reducing fluoroscopy time, and therefore radiation exposure, by the operator. 1250 It has been shown that use of optimized conventional fluoroscopy and optimized use of 3D mapping can result in a marked reduction in radiation exposure.…”
Section: Section 10: Complicationsmentioning
confidence: 99%
“…747,1186,1248,1249 This can only be achieved, however, by an awareness of the importance of reducing fluoroscopy time, and therefore radiation exposure, by the operator. 1250 It has been shown that use of optimized conventional fluoroscopy and optimized use of 3D mapping can result in a marked reduction in radiation exposure.…”
Section: Section 10: Complicationsmentioning
confidence: 99%
“…The end-points of interest were the incidence of in-hospital AF complications, long-term recurrence, multivariate risk for recurrence according to the AF type, and adjusted predictors for recurrence. 5 selection, adjudication, detection, and attrition bias (expressed as low, moderate, or high risk of bias, as well as incomplete reporting leading to the inability to ascertain the underlying risk of bias).…”
Section: Data Extractionmentioning
confidence: 99%
“…Multiple single center randomized studies and multicenter prospective registries comparing anti-arrhythmic drug therapy with TCAFA have shown significantly higher rates of patients in sinus rhythm after an invasive strategy at one year of follow up [1], [2], [3], [4], [5] and [6].…”
Section: Introductionmentioning
confidence: 99%
“…Integration of cardiac imaging using MRI and computed tomography was shown to further reduce fluoroscopy exposure during ablation procedure. 1 More recently, a new technology for catheter visualization called the MediGuide technology (St Jude Medical Inc, St Paul, MN) has been introduced that can further facilitate reduction in radiation exposure.…”
mentioning
confidence: 99%